Fine Needle Aspiration Cytology of Pigmented Dermatofibrosarcoma Protuberance (Bednar Tumor) & it’s Pathogenesis - Haque, Anwar Ul; Farooq, Hajra; Sharif, Maryam; Chaudhary, Sidra (International Journal of Pathology, 2018)
Dermatofibrosarcoma protuberance is a soft tissue tumor of low malignant potential. At times it isassociated with pigment deposits which are then it is termed as Bednar tumor. Only a few Fine Needle AspirationCytology studies of Bednar Tumor have been reported. We share our findings of Fine Needle AspirationCytology in a 30 year old man with Bednar tumor of scalp and multiple enlarged cervical lymph nodes. Oursmears revealed scattered atypical large round to oval cells with scant cytoplasm. Some cells’ cytoplasmcontained abundant melanin pigment which also resulted in dirty black pigmented background. The tissuesections showed melanin in both spindle shaped cells and rounded cells. At places it seemed that heavilypigmented cells became oval and globular and necrotic. The melanin pigment was extended into the cellularprocesses. The overlying skin epidermis shows focal kilocytotic type change. The tissue sections showedpositivity for CD 34 and protein S-100. We propose that round globular cells are derived from spindly cells aftermelanin synthesis and when the cytoplasm is overloaded with melanin the cells undergo necrosis. Focalkilocyototic type change in overlying epidermis deserves further investigation.